"Perrotta Human Defense Mechanisms Questionnaire" (PDM-Q): The new psychodiagnostic tool to identify human psychological defense mechanisms and their clinical implications - Giulio Perrotta (Archives of Depression and Anxiety - Peertechz Publications, 2021)
Starting from the models proposed on the subject of defense mechanisms by Perry-Vaillant, Gleser-Ihilevich, Bond, Haan, Plutchik, Carver and Johnson-Gold, this research focuses attention on the need to respond to the need for a better structure than the current psychodynamic tools, in a functional framework, in terms of defense mechanisms, starting from the nosographic schemes of the Perrotta Integrative Clinical Interviews (PICI-2) and the emotional framework of the Perrotta Human Emotions Model (PHEM) that studies basic emotions and emotional-behavioral reactions. For this reason, with 24 closed multiple-choice narrative questions, on a 0-5 scale, the Perrotta Human Defense Mechanisms Questionnaire (PDM-Q) allows to identify which defense mechanisms the patient uses the most and their degree of functioning, starting from the central role of emotions. The paradigm at the basis of the PDM-Q (able to identify 24 defense mechanisms, in their 28 functional and 59 dysfunctional forms) is therefore to work directly on the emotional states and on the emotional-behavioral reactions of the patient to identify the individual defense mechanisms and their degree of functioning or habitual dysfunction, based on the factual circumstances.